CdSe/ZnS quantum dot-encoded maleic anhydride-grafted PLA microspheres prepared through membrane emulsification for multiplexed immunoassays of tumor markers. Issue 9 (14th April 2022) - Tang, Wan-Sheng; Zhang, Bo; Xu, Lai-Di; Bao, Ning; Zhang, Qing; Ding, Shou-Nian
Abstract : Liquid suspension biochips based on quantum dots (QDs) encoded microspheres have been widely used in the immunodetection of tumor markers. Abstract : Early diagnosis of tumor markers is of great importance for the successful treatment of cancer. As a high-throughput and high-sensitivity detection technology, liquid suspension biochips based on quantum dot (QD) encoded microspheres have been widely used in the immunodetection of tumor markers. In this work, maleic anhydride grafted PLA (PLA-MA) microspheres based on quantum dot encoding were used as carriers for liquid phase suspension biochips for the immunoassay of tumor markers. PLA-MA fluorescent beads are prepared by embedding CdSe/ZnS quantum dots in PLA-MA using Shirasu porous glass (SPG) membrane emulsification technology, which has high fluorescence intensity, good stability, and good dispersion. Fluorescent immunoassays on dipsticks found that PLA-MA microspheres have high biological activity and good stability, which is conducive to immunoassays. Based on this, using the characteristics of CdSe/ZnS quantum dots and flow cytometry, monochromatic and two-color coding methods were developed, and 9 distinguishable coding beads were prepared. The results showed that PLA-MA fluorescent microspheres exhibited good biocompatibility, stable coding signals, low background noise, and low detection limits when performing quaternary immunoassays on tumor markers CA125, CA199, CA724, and CEA by CdSe/ZnS QD-encoded PLA-MA microsphere binding flow cytometry.